THE HISTORY OF INTONATION AND COMPONENTS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
Intonation, or the melody and pitch movement of spoken language, is one of the cornerstones of effective communication. It supports speakers in the transfer of shades of meaning, such as emotional tone, intention, and emphasis, which go far beyond the conventional meaning of words. This article will provide an in-depth overview of the historical development of intonation studies, the structural elements constituting intonation, and the manifold functions of intonation in language. This article insists on the importance of intonation in the context of language teaching and phonology, outlining how intonation reaches its purpose, which is to shape spoken interactions and give rise to communication efficacy.